THE WATER SECURITY MANAGEMENT AND ITS INFLUENCE TOWARDS INTER-STATE CONFLICT IN THE MIDDLE EAST REGION - M. Yudha Hawaril Umam; Bayu Mitra Adhyatma Kusuma (UIN Sunan Kalijaga, 2015)
Water is an irreplaceable element in the human life. Water security was alwayspursued by each country to ensure the prosperity of its people. But in fact, more thana third of the world’s population needs of fresh water are not fulfilled, both for drinkingand sanitation. So that’s why water security management is urgent to implement.That problem was happened in the Middle East region until today. As we know thatmost of the Middle East region is composed from the barren desert. Although underthe desert there are abundant of oil, but the water is a problem for most of the MiddleEast region. Middle East region needs a constant water supply approximately 127.5billion cubic meters per year. Such conditions involve in water scarcity and inter-stateconflicts caused by the water. Conflict in the struggle for water resources is difficult toavoid because the water needs in the Middle East region is bigger than the wateravailability. Those inter-state conflict involving various countries including Israel, Egypt,Jordan, Palestine, Lebanon, and Syria. Appropriate and equitable solutions shouldbe formulated and implemented, such as making water management agreement whichmust be agreed by all countries. Because if not addressed, the seizure of water resourcescan be lead to high tension, conflict, or even war in the Middle East region. Toelaborate the data, this research uses qualitative method, descriptive analysis approach,and emphasize on the literature study.Keywords: Water Security Management, Inter-State Conflict, Middle East